Financial Innovation: Alternatif 'Menjanjikan' dalam Dunia Keuangan - Bertha . (Jurnal Manajemen Maranatha, 2008)
Financial innovation has more influences for company and investor who want to borrow or lending. Financial economics, law and regulator, technology change, etc. exactly will be influences successful of financial innovation. Stimulated financial innovation was importance so that could achieve maximum success. Financial market especially capital market also being more efficient and effective. But it had been supported improvement society knowledge about how financial innovation arising, why sometimes success or fail, what function and benefit from this, determining factors, and relationship with market price and asset pricing. In emerging market, financial innovation has effect to growth economic and decrease national‟s cost of capital. Social welfare will achieve because had been transfer from saving to investing until the end can decrease household cost of living.